Small Heat Shock Protein αB-Crystallin Controls Shape and Adhesion of Glioma and Myoblast Cells in the Absence of Stress. - Miho Shimizu; Mikihito Tanaka; Yoriko Atomi (PLoS ONE, 2016)
Cell shape and adhesion and their proper controls are fundamental for all biological systems. Mesenchymal cells migrate at an average rate of 6 to 60 μm/hr, depending on the extracellular matrix environment and cell signaling. Myotubes, fully differentiated muscle cells, are specialized for power-generation and therefore lose motility. Cell spreading and stabilities of focal adhesion are regulated by the critical protein vinculin from immature myoblast to mature costamere of differentiated myotubes where myofibril Z-band linked to sarcolemma. The Z-band is constituted from microtubules, intermediate filaments, cell adhesion molecules and other adapter proteins that communicate with the outer environment. Mesenchymal cells, including myoblast cells, convert actomyosin contraction forces to tension through mechano-responsive adhesion assembly complexes as Z-band equivalents. There is growing evidence that microtubule dynamics are involved in the generation of contractile forces; however, the roles of microtubules in cell adhesion dynamics are not well determined. Here, we show for the first time that αB-crystallin, a molecular chaperon for tubulin/microtubules, is involved in cell shape determination. Moreover, knockdown of this molecule caused myoblasts and glioma cells to lose their ability for adhesion as they tended to behave like migratory cells. Surprisingly, αB-crystallin knockdown in both C6 glial cells and L6 myoblast permitted cells to migrate more rapidly (2.7 times faster for C6 and 1.3 times faster for L6 cells) than dermal fibroblast. On the other hand, overexpression of αB-crystallin in cells led to an immortal phenotype because of persistent adhesion. Position of matured focal adhesion as visualized by vinculin immuno-staining, stress fiber direction, length, and density were clearly αB-crystallin dependent. These results indicate that the small HSP αB-crystallin has important roles for cell adhesion, and thus microtubule dynamics are necessary for persistent adhesion.